'Reductionistic' and 'Holistic' Views of Resource‐Based Theory: A Review of the Literature1. (November 2015) - Rashidirad, Mona; Soltani, Ebrahim; Salimian, Hamid
Abstract : In contrast to the 'reductionistic' approach, a 'holistic' approach to resource‐based theory has the ability to address the complex interrelationships among multiple organizational characteristics, competitive strategies, and performance.